Sistem Pendukung Keputusan Pemberian Kredit Usaha Rakyat Menggunakan Metode Weighted Aggregated Sum Product Assesment (WASPAS) - Ickhsan, Muhammad; Anggraini, Dewi; Haryono, Rocky; Sahir, Syafrida Hafni; Rohminatin, Rohminatin (STMIK Budi Darma, 2018)
Decision Support System (DSS) is a system that can assist a person in making decisions that are accurate and targeted. To assist in determining the eligibility of the recipients of the People's Business Credit (KUR), a decision support system is required. In this research, Weighted Aggregated Sum Product Assessment (WASPAS) method is used to determine the eligibility of KUR recipient customers. There are several criteria which are the basis for decision making such as credit status, business productivity, business condition, guarantee, and collectibility. Credit status means the KUR recipient is not receiving KUR elsewhere. Productivity means whether the business is productive or not, in terms of business location, type of business, and monthly income. Business condition means whether the business is running in good condition or not, seen from business management, business equipment, and Human Resources (HR). Collateral means collateral in the form of what will be used as collateral, such as house/shop, land, and BPKB. While collectibility means the smoothness of prospective recipients of KUR in paying monthly installments.